2022
DOI: 10.47481/jscmt.1157026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbon fiber reinforced conductive mortars filled with recycled ferrochrome slag aggregates

Abstract: Recently, it is known that carbon fiber, which is a conductive fiber, is used in different mixture designs and developing electrically conductive cementitious materials. However, the evaluation of ferrochrome as a recycled aggregate in the mixture of these special concretes has still not been investigated. In this study, electrically conductive mortars were produced by using 100% recycled ferrochrome aggregate with a particle size of less than 1 mm as filling material and using carbon fiber (CF) in 4 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…7, the conductive CNT particles contributed to the conductivity of the composite material by creating an electric field [66]. When the EDS results are compared with the cemented studies in the literature, the peaks and their grades have been confirmed by the results of several studies [67,68]. In Fig.…”
Section: Refmentioning
confidence: 64%
“…7, the conductive CNT particles contributed to the conductivity of the composite material by creating an electric field [66]. When the EDS results are compared with the cemented studies in the literature, the peaks and their grades have been confirmed by the results of several studies [67,68]. In Fig.…”
Section: Refmentioning
confidence: 64%